Inflammatory cytokine expression is associated with chikungunya virus resolution and symptom severity. - Alyson A Kelvin; David Banner; Giuliano Silvi; Maria Luisa Moro; Nadir Spataro; Paolo Gaibani; Francesca Cavrini; Anna Pierro; Giada Rossini; Mark J Cameron; Jesus F Bermejo-Martin; Stéphane G Paquette; et al. (Public Library of Science (PLoS), 2011)
The Chikungunya virus infection zones have now quickly spread from Africa to parts of Asia, North America and Europe. Originally thought to trigger a disease of only mild symptoms, recently Chikungunya virus caused large-scale fatalities and widespread economic loss that was linked to recent virus genetic mutation and evolution. Due to the paucity of information on Chikungunya immunological progression, we investigated the serum levels of 13 cytokines/chemokines during the acute phase of Chikungunya disease and 6- and 12-month post-infection follow-up from patients of the Italian outbreak. We found that CXCL9/MIG, CCL2/MCP-1, IL-6 and CXCL10/IP-10 were significantly raised in the acute phase compared to follow-up samples. Furthermore, IL-1β, TNF-α, Il-12, IL-10, IFN-γ and IL-5 had low initial acute phase levels that significantly increased at later time points. Analysis of symptom severity showed association with CXCL9/MIG, CXCL10/IP-10 and IgG levels. These data give insight into Chikungunya disease establishment and subsequent convalescence, which is imperative to the treatment and containment of this quickly evolving and frequently re-emerging disease.